Pengaruh Strategi Pembelajaran Problem Based Learning dan Kemampuan Berpikir Kritis Terhadap Hasil Belajar Fiqih - Rini Fitri Agustia; Sulaiman Sulaiman (Prodi Pendidikan Keagamaan Islam, 2023)
This research was motivated by the low learning outcomes of Fiqh students in class VII at MTsN 3 Padang Pariaman. Among the factors that cause low student learning outcomes are the learning strategies applied and the level of students' critical thinking skills. This study aims, firstly, to find out how the process of PBL strategy is in class VII Fiqh subjects, secondly, to find out the value of critical thinking skills in Fiqh class VII subjects, thirdly, to find out how the use of PBL strategy and critical thinking skills influences the learning outcomes of Fiqh class VII students. . This research is quantitative with correlational research methods. The results showed that there was an effect of the PBL strategy variable on the learning outcomes of Jurisprudence class VII 3 by 46.1% and class VII 4 by 13.8%. As for the variable critical thinking skills on learning outcomes of Jurisprudence class VII 3 of 10.4% and class VII 4 of 10.7%, then there is a joint effect of PBL strategy variables and critical thinking skills of class VII 3 of 10.9% and class VII 4 of 04.3%. It can be concluded that there is an influence of PBL strategy variables and critical thinking skills on Fiqh learning outcomes Fiqh learning outcomes for class VII students at MTsN 3 Padang Pariaman. Based on the results of the data analysis, the PBL strategy and critical thinking skills can be applied in the teaching and learning process in schools to improve student learning outcomes.